Regresja ortogonalna i klasyfikacja - Miszczak, Witold (The Orthogonal Regression and Classification, 2006)
In this paper the well-known problem of estimating parameters of linear orthogonal regression have been presented. There are proposed any methods of estimating the eigenvectors for the symmetrical and unsymmetrical matrices without calculating its eigenvalues. Additionally there is given an algorithm for classification sample data obtained from no homogenous population in which subpopulations are stepping out with diverse equations of the orthogonal regression.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 111-123